Pendampingan public speaking pada tutor lembaga kursus bahasa Inggris - Siti Ayu Surayya; Maman Asrobi; Ari Prasetyaningrum (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2020)
Based on the observations' results, many graduate students from an English course institution still do not understand public speaking techniques. Even though the course institution is a well-known course institution in Indonesia, these graduates are relatively fast reading and speaking English. However, this word's smooth production was not matched with variations in voice, changes in intonation, and minimal meaning. As a lecturer in the English department, this is also our responsibility. Moreover, these graduates are now having their English course institutions independently. They are required to be able to communicate with their students. It is hoped that the current course institutions, especially in the Selong sub-district, can improve the quality of learning by applying correct public speaking techniques. Therefore, it is necessary to hold public speaking training for tutors at English language course institutions. The service plans carried out are: 1.) Delivery of mentoring material, 2.) Implementation of speaking practice in internal forums, 3.) Study tours at other course institutions, 4. ) Practicing speaking as well as evaluating outside the forum. This community service has increased English tutors' understanding in the Foreign Language Center (FLC) of Selong sub-district, East Lombok, seen from how they apply public speaking techniques during their teaching practice English tutors